2013
DOI: 10.5455/ijmsph.2013.270820132
|View full text |Cite
|
Sign up to set email alerts
|

Gender preference and awareness regarding sex determination among pregnant women - A hospital based study

Abstract: Background: Sex ratio, an important social indicator measuring extent of prevailing equity between males and females in society. Aims & Objective: To find out awareness regarding sex determination and attitude towards gender preference among pregnant women. Material and Methods: A cross-sectional, hospital-based, descriptive study was undertaken among pregnant women who attended the antenatal clinic. Information recorded regarding on the sociodemographic factors viz. education of study subjects, socioeconomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 6 publications
3
13
2
Order By: Relevance
“…2 Studies across India have revealed varying degrees of male preference from 27% to 41%. [3][4][5] It is understood that preference for male child is a function of various sociodemographic variables like education, social class, occupation, urban rural differences, with more developed societies being neutral towards sex preference. Given the high female literacy rate in Goa, late age at marriage, late age at first pregnancy and being primarily an urban state the figure of 63% being neutral in terms of their sex preference during the pregnancy is not beyond expectation.…”
Section: Discussionmentioning
confidence: 99%
“…2 Studies across India have revealed varying degrees of male preference from 27% to 41%. [3][4][5] It is understood that preference for male child is a function of various sociodemographic variables like education, social class, occupation, urban rural differences, with more developed societies being neutral towards sex preference. Given the high female literacy rate in Goa, late age at marriage, late age at first pregnancy and being primarily an urban state the figure of 63% being neutral in terms of their sex preference during the pregnancy is not beyond expectation.…”
Section: Discussionmentioning
confidence: 99%
“…A study shows that 74% of the subjects knew about sex determination methods. 6 It was 11.66% in a study done by Puri et al in Chandigarh. 1 We have also found that about 79% of the men were aware about prenatal sex determination whereas it was 73.5% in a study done by Pallavi et al and 91.7% in a study done by Kumar on pregnant women in Mangalore (2014).…”
Section: Discussionmentioning
confidence: 94%
“…6 While assessing the knowledge about decline in sex ratio in our country, we have found about 27% were aware of decline in sex ratio. A study done in Bangalore by Pavithra showed 37% knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…The pregnant women expressed no preference or preference of one of the gender of their fetuses were seen in various studies. [5][6][7] The studies from western countriesshowed preference of the pregnant women to have a girl, 8 and men's desire to have a son as their first child.…”
Section: Introductionmentioning
confidence: 99%
“…11 Most pregnant women wish to know the gender of their fetuses 12,13 , but awareness of the methods of determination of prenatal sex of the fetuses is also high in different communities. 5,14 This study was done to find out the gender preference of pregnant women for their first baby, the number of children they want to have, their knowledge of prenatal sex determination, wish to know the gender of the unborn fetus, and the impact of education levels of the women on both their preference of gender and desire to know the gender of unborn fetuses.…”
mentioning
confidence: 99%